Pseudohypoparathyroidism with Ectopic Calcification and 22q11 Deletion Syndrome: A Rare Case - Diniz, Bruna Lixinski; Glaeser, Andressa Barreto; Deconte, Desirée; Guaraná, Bruna Baierle; Rosa, Rafael Fabiano Machado; Zen, Paulo Ricardo Gazzola (Journal of Pediatric Genetics, 2020)
Ectopic calcification in soft tissue is associated with several disorders including pseudohypoparathyroidism (PHP), which is characterized by resistance or nonresponse to parathyroid hormone (PTH) function. Association between PHP and 22q11DS, also known as DiGeorge syndrome, is rare, especially in children. We describe a newborn girl diagnosed with 22q11DS, presenting ectopic calcifications in soft tissue and suspicion of PHP. PTH function showed values close to the upper limit of the reference value. Radiology showed bone callus in the right wrist. PHP can be a new clinical finding associated with 22q11DS. Parathyroid function investigation in individuals with 22q11DS, presenting bone dysmorphisms and/or calcium metabolism alterations, should be considered.
Keywords: ectopic calcification; pseudohypoparathyroidism; DiGeorge syndrome